1997
DOI: 10.1111/j.1540-8159.1997.tb03622.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Mechanisms Underlying Vasovagal Syncope in Young Subjects

Abstract: The occurrence of vasovagal fainting is common in young subjects, but the origin of the precipitating hemodynamic mechanisms involved remain a subject of considerable speculation. Vasovagal fainting is not a sudden onset phenomenon, early failure of vascular resistance responses occurs in faint-prone young subjects. The variability of hemodynamic responses during the actual faint is large, but the main mechanism operative during, is withdrawal of sympathetic outflow to blood vessels in skeletal muscle with imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 28 publications
(5 reference statements)
3
45
0
Order By: Relevance
“…Stroke volumes found in the present study were signi®cantly smaller during HUT compared with SUP, as found in previous studies (Rowell, 1993;Wieling et al, 1997). This is caused by blood pooling in the legs and splanchnic area during standing (Rowell, 1993), resulting in a diminished venous return.…”
Section: Circulatory Responsessupporting
confidence: 87%
See 1 more Smart Citation
“…Stroke volumes found in the present study were signi®cantly smaller during HUT compared with SUP, as found in previous studies (Rowell, 1993;Wieling et al, 1997). This is caused by blood pooling in the legs and splanchnic area during standing (Rowell, 1993), resulting in a diminished venous return.…”
Section: Circulatory Responsessupporting
confidence: 87%
“…This is caused by blood pooling in the legs and splanchnic area during standing (Rowell, 1993), resulting in a diminished venous return. The signi®cantly higher HR found in the present as well as in other studies (Wang et al, 1996;Wieling et al, 1997) partly compensates for this smaller stroke volume in an attempt to maintain cardiac output. The signi®cantly higher HR found in the present as well as in other studies (Wang et al, 1996;Wieling et al, 1997) partly compensates for this smaller stroke volume in an attempt to maintain cardiac output.…”
Section: Circulatory Responsessupporting
confidence: 78%
“…While VVS can occur in young and ostensibly healthy people 5 , it is important to validate our findings in populations more susceptible to VVS.…”
Section: Discussionmentioning
confidence: 80%
“…1,5 VVS accounts for >77% of reported syncope episodes and occurs more frequently in young individuals. 2 The incidence of VVS displays a daily pattern with a broad peak in the morning (6:00-12:00).…”
mentioning
confidence: 99%
“…19,20 This is caused by blood pooling in the legs and splanchnic area with the body upright, 19 resulting in a diminished venous return and, consequently, a decreased stroke volume via the Frank-Starling mechanism. The signi®cantly higher HR, found in the present as well as in other studies, 20,21 partly compensates this smaller stroke volume and reduces the decrease in cardiac output. Cardiac output and MAP were unaltered in AB during head-up tilt most likely due to a sympathetic nervous system-induced increase in total peripheral resistance.…”
Section: Circulatory Responsesmentioning
confidence: 99%